Screening of bioinsecticides against the cotton bollworm on cotton - Carrano-Moreira, Alberto Fabio; All, John (Pesquisa Agropecuaria Brasileira, 1995)
Four bioinsecticides and a synthetic pyrethroid were evaluated against the cotton bollworm (Heliothis zea Boddie, 1850), (Lepidoptera: Noctuidae) in laboratory. Treatments were: cypermethrin, Bacillus thuringiensis var. kurstaki Berliner (BT), Steinernema feltiae Weiser, Heliothis Nuclear polyhedrosis Virus (HNPV), Beauveria bassiana (Bals) and the untreated check, applied over 2,8 cm2 cotton leaf discs in three difficrent concentrations. Mortality rate was recorded at one, two, seven and nine days after treatment. The efficiency of the bioinsecticides was also tested in a green-house. Treatments were the same but instead of HNPV an experimental formulation of BT (Mycogen <!-- @page { margin: 2cm } P { margin-bottom: 0.21cm } -->®) was used. Each treatment consisted of four plants (Coker 310) sprayed with insecticide and infested with nine neonate larva. Results were evaluated seven days after treatment. In laboratory cypermethrin and BT showed a significant difference compared to control at day 1, despite concentrations. They did not differ statistically frorn each other. S. feltiae showed a significant mortality rate to control after day 2. HNPV was highly effective between two and seven days after treatment, killing all larvae. In green-house cypermethrin showed a significant difference compared to check.